2016
DOI: 10.1155/2016/6179805
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Migraine: Clinical Challenges and Opportunities for Multidisciplinarity

Abstract: Migraine and vertigo are two very prevalent conditions in general population. The coexistence of both in the same subject is a significant clinical challenge, since it is not always possible to understand whether they are causally related or associated by chance, requiring different diagnostic and therapeutic approaches. In this review we analyze and summarize the actual knowledge about vestibular migraine (VM), focusing on the new concepts proposed by the International Classification of Headache Disorders 3-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 95 publications
0
11
0
Order By: Relevance
“…Since vestibular migraine has only recently emerged as a diagnostic category, there are few epidemiological studies available at present (Luzeiro et al 2016). Nonetheless, Radtke et al (2012) reported that a vestibular migraine occurred more frequently in women during the fourth decade of life.…”
Section: Vestibular Migrainementioning
confidence: 99%
“…Since vestibular migraine has only recently emerged as a diagnostic category, there are few epidemiological studies available at present (Luzeiro et al 2016). Nonetheless, Radtke et al (2012) reported that a vestibular migraine occurred more frequently in women during the fourth decade of life.…”
Section: Vestibular Migrainementioning
confidence: 99%
“…[ 11 ] Familial occurrence has been reported in some patients with an autosomal dominant pattern of inheritance and decreased penetrance in men. [ 12 ]…”
Section: S Earch M Ethodsmentioning
confidence: 99%
“…[ 13 ] The headache might be from moderate to severe. [ 12 ] However, nearly 30% of VM attacks found no associated headache. Only a quarter or less of the patients tend to have throbbing migraine attacks.…”
Section: S Earch M Ethodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate diagnosis of vertigo in migraine is complicated by the similarity and combination of groups of symptoms. In accordance with the provisions of the International Classification of Headache, 3 rd edition (ICHD-3) published criteria for migraine-associated vertigo (migrainous vertigo, migraine-associated dizziness), developed jointly with the International society for the study of headache and the Barani Society (Furman and Balaban, 2015;Luzeiro et al, 2016;O'Connell Ferster et al, 2017;).…”
Section: Introductionmentioning
confidence: 99%